2006
DOI: 10.1177/0959683606hl989rp
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene coastal hydrographic and climate changes in the eastern North Sea

Abstract: We present a high-resolution palaeoenvironmental reconstruction covering the late Holocene from the Skagerrak and other sites in the North Sea area. The data, which are based on the analyses of marine sediment cores, reveal a marked environmental shift that took place between AD 700 and AD 1100, with the most pronounced changes occurring at AD 900. Both surface and bottom waters in the Skagerrak were subject to major circulation and productivity changes at this time due to an enhanced advection of Atlantic wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 58 publications
4
31
0
Order By: Relevance
“…The high oxygen and favourable nutrient conditions were likely associated with an intense mixing of the water column and enhanced productivity. Gil et al 15 (2006) and Hebbeln et al (2006) suggested increased storminess that entailed intense mixing of the water column at this time (Erbs-Hansen et al, 2011), in line with our results. The colder BWTs at both sites can be indicative of weaker Atlantic water inflow.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The high oxygen and favourable nutrient conditions were likely associated with an intense mixing of the water column and enhanced productivity. Gil et al 15 (2006) and Hebbeln et al (2006) suggested increased storminess that entailed intense mixing of the water column at this time (Erbs-Hansen et al, 2011), in line with our results. The colder BWTs at both sites can be indicative of weaker Atlantic water inflow.…”
supporting
confidence: 83%
“…This interpretation is 30 supported by a study from the Northern North Sea, where Klitgaard-Kristensen and Sejrup (1996) argued that the Atlantic water is favourable for planktonic foraminifera, while the low salinity of the NCC reduces their abundance. Our interpretation is further supported by previous studies based on foraminiferal (Erbs-Hansen et al, 2011) and diatom assemblages, as well as a multiproxy study by Hebbeln et al (2006), which all report on an onset of enhanced Atlantic water advection to the Skagerrak at ~ CE 900. Gil et al (2006), documented an increase in diatom species associated with high 5 salinity water in the Skagerrak and argued for enhanced productivity caused by inflow of nutrient-rich, high-salinity water via the NJC.…”
supporting
confidence: 79%
“…Additionally, variations in sediment properties appear to be synchronous to environmental changes, that have been reconstructed from eastern North Atlantic records (e.g. Hebbeln et al, 2006), evidenced by complementary patterns in sediment parameters, such as grain-size, in records from these locations. This emphasises the significance of the GeoB 8903 record despite the high spatial variability of sediment properties and although the chronology of Little Ice Age, Medieval Warm Period, Dark Ages or Roman Warm Period, which is commonly applied to the Portuguese shelf records, can not be implemented here.…”
Section: Discussionmentioning
confidence: 97%
“…1), the Norwegian Atlantic Current (NwAC) which is mainly a continuation of the North Atlantic Current (NAC) and the Norwegian Coastal Current (NCC), which has its main source in the Skagerrak region (Hebbeln et al, 2006). The warm and saline Atlantic water (temperature¼ 6-9 1C, salinity ¼ 435) enters the Norwegian Sea through two major pathways, from the southwestern part by passing the Iceland-Faroe Ridge and from the southeast along the FaroeShetland Channel (Orvik et al, 2001;Orvik and Niiler, 2002).…”
Section: Study Area and Oceanographymentioning
confidence: 99%